ANALYSIS OF THE INFLUENCE OF UNEMPLOYMENT, WORK FORCE, AND TOTAL POPULATION ON POVERTY IN NORTH SUMATRA PROVINCE 2005-2020 - Sinaga, Erwin Satrio Hamonangan; Simanjuntak, Monica Emilina; Agitha Tarigan, Netania Perbi; Siregar, Rahmadani (Universitas Negeri Medan, 2023)
North Sumatra Province is experiencing problems in various sectors of life. The economic sector is one of the important sectors that influences the course of other sectors of life. poverty as one of the problems that arise in the economic sector is the focus of the studies examined in this study. The purpose of this study was to determine the effect of unemployment, labor force, and population on poverty in the province of North Sumatra. This study uses multiple regression analysis method, using secondary data as a source of study. The secondary data obtained will be processed using the eviews application. The results of the study show that unemployment and population each have a significant effect on poverty,